High Prevalence and Early Occurrence of Skeletal Complications in EGFR Mutated NSCLC Patients With Bone Metastases - Laganà, Marta; Gurizzan, Cristina; Roca, Elisa; Cortinovis, Diego; Signorelli, Diego; Pagani, Filippo; Bettini, Anna; Bonomi, Lucia; Rinaldi, Silvia; Berardi, Rossana; Filetti, Marco; Giusti, Raffaele; et al. (Frontiers in Oncology, 2020)
Objectives The prevalence of Skeletal Related Adverse Events (SREs) in EGFR mutated non-small cell lung cancer (NSCLC) patients with bone metastases, treated with modern tyrosine kinase inhibitors (TKIs), has been scarcely investigated. Materials and methods We retrospectively evaluated the data of EGFR mutated NSCLC patients with bone metastases treated with TKIs in 12 Italian centers from 2014 to 2019, with the primary aim to explore type and frequency of SREs. Results Seventy-seven out of 274 patients enrolled (28%) developed at least one major SRE: 55/274 (20%) bone fractures, 30/274 (11%) spinal cord compression 5/274 (2%) hypercalcemia. Median time to the onset of SRE was 3.63 months. Nine patients (3%) underwent bone surgery and 150 (55%) radiation therapy on bone. SREs were more frequently observed within the 12 months from TKI start than afterwards (71% vs 29%, p 0.000). Patient Performance Status and liver metastases where independently associated with the risk of developing SREs. Median TKI exposure and overall survival were 11 and 28 months, respectively. Bone resorption inhibitors were associated with a lower risk of death (HR 0.722, 95% CI: 0.504-1.033, p= 0.075) although not statistically significant at multivariate analysis. Conclusion Bone metastatic NSCLC patients with EGFR mutated disease, treated with EGFR TKIs, have a relatively long survival expectancy and are at high risk to develop SREs. The early SRE occurrence after the TKI start provides the rationale to administer bone resorption inhibitors.